Elastic-plastic analysis of bisteel i-section beams/Bimetalių dvitėjų sijų būvio analizė, įvertinant plastinių deformacijų įtaką - Jaras, Arūnas; Kačianauskas, Rimantas (Journal of Civil Engineering and Management, 2001)
The elastic-plastic analysis of simple bisteel i-section beam subjected to uniform distributed load (Fig 1) is considered in this paper. The bisteel beam presents a composition of high-strength steel inclusions for the flanges in the region of maximum stresses and of low-strength steel for remaining volume of the beam. The aim of the paper is development of the explicit analytical model for description of plastic regions with respect to different steel properties as well as to dimensions of high-strength inclusions. The geometrical linear approach and perfectly plastic material model have been assumed. The variation of the strength ratio of the both steels and the variation of the length of inclusion leads to different distributions of plastic regions in the web and the flanges (Fig 2). By fixing the depth of plastic penetration different explicit expressions (1–10) of the limit bending moment and plastic boundaries (11–18) presented in Fig 3 have been derived. After integration over elastic and plastic regions explicit expressions (19–21) of middle-span deflection have been derived. Influence of different dimensions and material properties are investigated and presented graphically on Figs 5–8. The proposed analytical model has been also tested numerically by the finite element method. The ANSYS code and tetrahedral elements have been used for these purpose (Figs 9–11). A good agreement between the proposed analytical model and numerical experiments has been obtained if the relative length of the high-strength inclusion does not exceed 60% (linc /l ≤ 0.6) (Fig 12). Outside the range of this limit the influence of shear stresses is growing and analytical model has to be corrected by additional terms. Article in Lithuanian. First Published Online: 30 Jul 2012